2019
DOI: 10.2134/agronj2017.12.0753
|View full text |Cite
|
Sign up to set email alerts
|

Alfalfa–Grass Mixtures in Comparison to Grass and Alfalfa Monocultures

Abstract: Core Ideas Alfalfa–grass mixtures are good alternative to alfalfa and grass monocultures. In the establishment year, alfalfa dominated the mixture, whereas as stands got older, grasses increased their contribution to the biomass. Alfalfa had higher crude protein, whereas grasses had higher fiber digestibility. Alfalfa–grass mixtures improved forage seasonal distribution. The most common binary mixture in the northern Great Plains is smooth bromegrass (Bromus inermis L.) (SBG) with alfalfa (Medicago sativa L.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 36 publications
8
25
1
Order By: Relevance
“…Our study revealed that a year × forage system interaction affected herbage accumulation of the different forage systems tested. Similar to the results of our study, herbage accumulation differences among forage treatments were more pronounced in the establishment year compared to the succeeding production year [37,49]. For the legume monocultures, that lack of year effect on herbage accumulation was in complete contrast to the grass monocultures and grass-legume mixtures that favored greater herbage accumulation in the second year.…”
Section: Herbage Accumulationsupporting
confidence: 88%
See 3 more Smart Citations
“…Our study revealed that a year × forage system interaction affected herbage accumulation of the different forage systems tested. Similar to the results of our study, herbage accumulation differences among forage treatments were more pronounced in the establishment year compared to the succeeding production year [37,49]. For the legume monocultures, that lack of year effect on herbage accumulation was in complete contrast to the grass monocultures and grass-legume mixtures that favored greater herbage accumulation in the second year.…”
Section: Herbage Accumulationsupporting
confidence: 88%
“…For the legume monocultures, that lack of year effect on herbage accumulation was in complete contrast to the grass monocultures and grass-legume mixtures that favored greater herbage accumulation in the second year. Hence, we surmised that the legumes had a faster rate of establishment and stability in this study environment compared to the grass monocultures and the grass-legume mixtures similar to the observation made by Aponte et al [37]. However, contrary to our assumption of the legumes in this study, Bork et al [50] reported that legumes (alfalfa and clover) were slow to reach maximum biomass production relative to the grasses.…”
Section: Herbage Accumulationsupporting
confidence: 85%
See 2 more Smart Citations
“…The alfalfa‐induced N input can prime the process of plant growth and recovery of grasses in spring and optimize total niche complementarity for water, light, and other nutrients (Nyfeler et al., 2009). Many studies have reported alfalfa–grass yield advantages of 15–45% over N‐fertilized grass monocultures (Aponte, Samarappuli, & Berti, 2019; Sanderson, Brink, Stout, & Ruth, 2013; Sleugh et al., 2000) or up to 143% over rangeland grass stands (Mortenson, Schuman, Ingram, Nayigihugu, & Hess, 2005). Nyfeler et al.…”
Section: Introductionmentioning
confidence: 99%